Spectrophotometric analysis of selected metal ions using microwave assisted in situ complexation. Issue 12 (26th September 2022) - Ali, Asif; Hussain, Zahid; Zahid, Muhammad; Qamar, Lubna; Zada, Amir; Arain, Muhammad Balal; Salman, Syed Muhammad; Khan, KhalidMohammed
ABSTRACT: A novel spectrophotometric method has been developed for the analysis of cadmium, cobalt, copper, iron and lead. This method is based on microwave-assisted in-situ complexation of metals ions with a ligand formed by the reaction of phenol, sodium nitrite and streptomycin in an acidic medium. The method was applied for the analysis of a variety of real samples including pharmaceuticals and industrially important products such as batteries. In this work, the wavelength for each of the metal complexes was scanned in the range of 400–800 nm. Each of this reaction was carried out in acidic medium; however, the amount of acid was found to vary with variation in the nature of metal ions. The optimum pH was 2.8 for iron, 6.5 for lead, 5.0 for copper, 5.5 for cobalt and 5.6 for cadmium. Keeping in view the difference in coordination number and difference in reactivity of metals, each of the reagents such as phenol, sodium nitrite and streptomycin were optimised for each of the metals separately. All experimental conditions such as optimum concentration of reagents and microwave heating time were optimised. It was observed that the optimum concentration of phenol is 8.99 mg/L for cadmium, cobalt and iron while that for lead and copper was 7.99 mg/L and 3.99 mg/L, respectively. The amount of sodium nitrite was found the same for each of the metals. In case of streptomycin, the optimum concentrations for each of cadmium and cobalt were found to be 0.988 mg/L and that for lead and iron were 1.498 mg/L, and 0.499 mg/L for cobalt. The limit of detection for each cadmium, cobalt, copper, iron and lead were found 0.0242, 0.0105, 0.1915, 0.1018 and 0.0185 mg/L, respectively. The limit of quantification for cadmium, cobalt, copper, iron and lead were determined as 0.0806, 0.0349, 0.6382, 0.3394 and 0.0615 mg/L, respectively. The developed method was successfully applied for the determination of selected metals in real samples.